CLINICAL AND PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF DIABETIC PATIENTS WITH INFECTED DIABETIC FOOT AT VIET TIEP FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics, paraclinical findings, and treatment outcomes of patients with diabetic foot infection treated at Department of Internal Medicine No. 3, Viet Tiep Friendship Hospital, Hai Phong, Vietnam, during 2023–2024.Subjects and Methods: A total of 65 inpatients with diabetic foot infection were included. This was a descriptive cross-sectional study using convenience sampling.Results: The mean age was 66.1 ± 11.5 years. The proportion of smokers was 29.2%, and 64.6% had hypertension. Clinically, most patients had Wagner grade 2–3 lesions (92.3%). The duration of ulcer prior to admission was
Keywords: Diabetes mellitus; diabetic foot infection; ankle–brachial index (ABI); peripheral arterial disease; arterial stenosis/occlusion